The effects of mild hypothermia on the electrode insertion trauma in a murine whole organ cochlea culture - Schmutzhard, Joachim; Bader, Werner; Gottfried, Timo; Dejaco, Daniel; Glückert, Rudolf; Dudas, Joszef; Schrott-Fischer, Annelies (Frontiers in Neuroscience, 2023)
Introduction Local therapeutic hypothermia (32°C) has been linked experimentally to an otoprotective effect in the electrode insertion trauma. The pathomechanism of the electrode insertion trauma is connected to the activation of apoptosis and necrosis pathways, pro-inflammatory and fibrotic mechanisms. In a whole organ cochlea culture setting the effect of therapeutic hypothermia in an electrode insertion trauma model is evaluated. Material and Methods The cochleae of C57Bl6/J mice (Charles River®, Freiburg, Germany) are cultured for 24 hours at 37°C and 32°C after inserting a fishing line through the round window simulating an insertion trauma. The resulting effect was evaluated for the apoptotic reaction – B-cell-Lymphoma-2-Associated-X-Protein (BAX), B-Cell-Lymphoma-2-Protein (BCL2) and Cleaved-Caspase-3 (CC3) –, the inflammatory response – Tumor-Necrosis-Factor-Alpha (TNFα), Interleukin-1-Beta (IL-1Imm) and Cyclooxygenase-2 (COX2) – and proliferation process – Transforming-Growth-Factor-Beta-1 (TGFβ1) – using immunohistochemistry and real-time PCR technique. A minimum of 12 cochlea per experiment were used. Results A pro-apoptotic situation was observed in the normothermic group (BAX, CC3 ˃ Bcl2) whereas an anti-apoptotic constellation was found at 32°C culture conditions (BAX, CC3 < Bcl2). Furthermore the effect of the IT knowing to effect the pro-inflammatory cytokine (TNFα, Il1β) and enzyme (COX2) expression has been reproduced. This reaction was reversed with the application of therapeutic hypothermia resulting in significant lower pro-inflammatory cytokine (TNFα, Il1β) and enzyme (COX2) expression. TGFβ1 was increased by hypothermia. Discussion Concluding a protective effect of hypothermia on the experimental electrode insertion trauma can be described by an anti-apoptotic and anti-inflammatory reaction.